THE EFFECT OF GIVING GREEN COCONUT WATER ON REDUCING DYSMINORHEA PAIN IN ADOLESCENT GIRLS AT SMPN 3 PARIAMAN IN 2024 - DELINDA B, DIVA; RISHEL, RIKA ASTRIA; YUNTARISA, ATIKA PRADANA (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2024)
Introduction: Dysminorrhea pain is an imbalance of the hormone progesterone in the blood, resulting in abdominal pain caused by uterine muscle spasms. Young coconut water contains growth hormone, magnesium and calcium which can reduce muscle tension and vitamin C which is a natural anti-inflammatory substance which can help relieve pain due to menstrual cramps. Method: Quasi-experimental research design with non-randomized one group pretest and posttest design. The aim is to determine the effect before and after giving young green coconut water on dysmenorrhea pain. Sampling was taken using a proportional sampling technique with a total of 30 respondents. Results: Statistical test using data analysis using Shapiro-Wilk and Wilcoxon with significance (p<0.05) and a significant value of Pvalue 0.000, thus Ho was rejected. Conclusions and Suggestions: There is an effect of giving young green coconut water on dysmenorrhea pain in teenagers. Researchers recommend that teenagers who experience menstrual pain consume young green coconut water on the first day of menstruation